The Pathogenetic Basis of the Action of Bempedoic Acid - A. S. Petrosyan; R. S. Rud'; P. P. Polyakov; A. Kh. Kade; S. A. Zanin (Столичная издательская компания, 2023)
The modern cardiology has a wide range of medications which affect various pathogenetic links of atherosclerosis, but even the best of them still obtain disadvantages causing intolerance and medicine discontinuation. The development of new hypolipidemic medications will allow not only to introduce alternative therapies into the cardiology practice, but also to completely execute the strategy of residual risk reduction by utilizing rational combinations of medications. One of such alternatives could be bempedoic acid, which can have a positive effect on a number of endpoints as the results of third phase trials have shown. These effects are also confirmed in Mendelian randomization studies. The mechanism of action of bempedoic acid is presumably associated with inhibition of the activity of ATP citrate lyase - the enzyme responsible for the breakdown of citrate into acetyl-CoA and oxaloacetate. Acetyl-CoA, in turn, is used by the cell to synthesize cholesterol and fatty acids. Thus, bempedoic acid affects in the same metabolic pathway as statins, but at an earlier stage. According to this, it is possible that medications of these classes will have similar side effects and pleiotropic effects associated with modulation of the mevalonic pathway, such as prenylation regulatory proteins (small GTPases) or reduction of coenzyme Q synthesis. However, there are also some specific features of the pharmacodynamics and pharmacokinetics of bempedoic acid to be considered. In particular, once entered the body, it must be activated via esterification by very long-chain acyl-CoA synthetase-1. The enzyme isoform required for this process is expressed in a tissue-specific manner and, for example, is absent in skeletal myocytes. In addition, citrate, oxaloacetate, and acetyl-CoA are important regulators of many intracellular processes: metabolism, growth and proliferation, mechanotransduction, posttranslational modifications of histones and other proteins. The levels of all three substances are altered by bempedoic acid, although no firm conclusions about the effects of these changes can be drawn at this time. The mentioned features probably have a significant impact on the clinical profile of bempedoic acid and underlie the differences from statins already observed in third phase trials, including, for example, a reduced risk of the onset or worsening of diabetes mellitus while taking bempedoic acid.